A possible modulatory role for prostacyclin (PGI2) INIgGa-induced release of slow-reacting substance of anaphylaxis in rats. - Burka, J F (1977)
Antigen challenge in vivo of rat peritoneal cells (enriched with monocytes and polymorphonuclear leucocytes) passively sensitized 2 h previously with homologous antibody of the IgGa class released large amounts of slow-reacting substance of anaphylaxis (SRS-A, 1739 +/- 59 u/ml) into the peritoneal fluid. This reaction was strongly inhibited by prostacyclin (PGI2, ED50 = 0.5 microgram/kg i.p.) and by isoprenaline (ED50 = 0.2 microgram/kg i.p.) but prostaglandins E1, E2 and 6-oxo-prostaglandin F1alpha were only weak inhibitors. Indomethacin (10 mg/kg, orally) augmented by 30% the release of SRS-A, whereas thromboxane B2 (50 microgram/kg i.p.) had no effect. Lowering the antigen (ovalbumin) dosage from 400 microgram/ml to 10 microgram/ml reduced the control release of SRS-A by 70% and increased the inhibitory effect of prostaglandins I2, E1 and isoprenaline. Augmentation of release by indomethacin remained unchanged. These preliminary data suggested that endogenous prostacyclin may modulate the anaphylactic release of SRS-A from rat peritoneal cells.